PELATIHAN PENINGKATAN DAYA TRANSFER PENGETAHUAN MELALUI LITERASI KOMPUTER PADA PESANTREN EL JASMEEN DI KEL. BANJARARUM KEC. SINGOSARI KAB. MALANG - sonhaji sonhaji; Lidia Andiani; Mohammad Syadeli; Muslichah Muslichah; Uke Prayoga (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
This article aims to show that educators' transfer power to students can be increased through educators' computer literacy. The development of science and technology has gained momentum by discovering and developing the internet and its supporting facilities. The development commonly known as information and communication technology provides effectiveness for life activities, especially in education. Due to an increase in the use of ICT in education and educational institutions, computer literacy is a must for educators and education personnel to carry out their duties. This article seeks to reveal the increase in the transfer of educators' knowledge and the effectiveness of the teaching staff's duties from community service activities in Islamic boarding schools. The community service activities that have been carried out to the educators and education personnel show an increase in the capacity of teaching materials provided to students and the capacity for student’s acceptance. Besides, the increase in computer literacy promotes effectiveness and easiness for the educators in fulfilling the tasks as part of their responsibility.